AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING HORTATORY EXPOSITION - AFRA NADYA PUTRI INSANI (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study aims at analyzing students’ ability in writing hortatory exposition based on the generic structure. The research design was descriptive methods. The researcher chose eleventh grade students in SMA Negeri 5 Malang especially in cross interest class (kelas Lintas Minat) which consists 29 students as the subject of the research. The data was collected by students’ assignment in writing hortatory exposition. The findings of this research stated that the ability of  eleventh grade students of SMA Negeri 5 Malang  in writing hortatory exposition based on the generic structure were in “Good” category with the mean 72. There are 6 students were in “Very Good” category, 16 students were in “Good” category, 4 students in “Fair” category, and 3 students were in “Poor” category which wrote the hortatory exposition based on the generic structure. The researcher concludes that the students’ ability in writing hortatory exposition text based on the generic structure categorized as good with the mean was 72. Based on research findings, it is addressed to the students to learn more the generic structures of hortatory exposition and the teacher must investigate approaches or methods for teaching hortatory exposition text so that students can understand the topic. It is also needed to further exploration and investigation about analysis students’ ability in writing hortatory exposition in other future research.